2018
DOI: 10.1016/j.anireprosci.2018.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estrous cycle phase on vulvar, orbital area and muzzle surface temperatures as determined using digital infrared thermography in buffalo

Abstract: The objective of this study was to evaluate variations in the orbital area, muzzle and vulva surface temperatures and progesterone (P4) concentrations during follicular and luteal phases in Murrah buffalo and whether these temperatures are influenced by the weather patterns. Forty cows were submitted to P4-based hormonal protocol. After P4 device withdrawal transrectal ultrasonography and infrared digital thermography were performed daily until day 16 and on days 20, 24, 28 and 32 to follow the ovulation as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
3
8
0
Order By: Relevance
“…Studies of the river buffalo have reported a similar response, according to findings by Ruediger et al [ 78 ], who evaluated temperature oscillations in the vulva and progesterone concentrations in 40 Murrah buffaloes in a synchronization protocol with progesterone. They observed that the temperature of the vulva increased during estrus and maintained an inversely proportional correlation to progesterone levels (r 2 = 0.70); that is to say that progesterone levels increased to the degree that the temperature of the urogenital region ( regio urogenitalis ), especially the vulva, decreased.…”
Section: Perineal Region ( Regio Perinealis )supporting
confidence: 58%
See 1 more Smart Citation
“…Studies of the river buffalo have reported a similar response, according to findings by Ruediger et al [ 78 ], who evaluated temperature oscillations in the vulva and progesterone concentrations in 40 Murrah buffaloes in a synchronization protocol with progesterone. They observed that the temperature of the vulva increased during estrus and maintained an inversely proportional correlation to progesterone levels (r 2 = 0.70); that is to say that progesterone levels increased to the degree that the temperature of the urogenital region ( regio urogenitalis ), especially the vulva, decreased.…”
Section: Perineal Region ( Regio Perinealis )supporting
confidence: 58%
“…Studies of the river buffalo have reported a similar response, according to findings by Ruediger et al [78], who evaluated temperature oscillations in the vulva and progesterone concentrations in 40 Murrah buffaloes in a synchronization protocol with progesterone.…”
Section: Perineal Region (Regio Perinealis)supporting
confidence: 58%
“…Although Nelore bulls presented lower volume of ejaculate, it had higher sperm concentration, sperm motility and sperm vigor, lower incidence of sperm defects and greater TTR resistance than Girolando bulls (Table 5). Ruediger et al (2018) observed that body surface temperatures measured with the thermograph can be used to identify heat stress due to the positive correlation of these points with rectal temperature and plasma cortisol levels. Weschenfelder et al (2013) found that imaging the eye surface allows the detection of temperature changes associated with physiological conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is interesting to know whether the temperature readings of different ROIs of the eye are repeatable across a heat stress event. As for the validity of ET in revealing heat stress in dairy cows, lots of studies have demonstrated a mild to strong correlation of ET with RR and CBT ( 10 , 16 , 17 ). Bleul et al ( 17 ) reported that the maximum temperature of the entire eye, rather than the medial canthus (MC), had the highest correlation coefficient with the rectal temperature in 30 cows.…”
Section: Introductionmentioning
confidence: 99%